Taxiway Guidance Sign Jenis Mandatory Instruction Sign - Taryana; Achmad Mahesa; Asep Samanhudi (Politeknik Penerbangan Makassar, 2022)
With the development of science and technology, the use of Light Emitting Diode (LED) lamps. The use of LEDs has the advantage of durable use, the use of electricity is 60% more efficient than Tube Lamps (TL), the light produced is close to perfect and does not cause heat. The working principle is that the original input voltage in the form of AC voltage is changed by the rectifier circuit so that the output becomes DC voltage. The purpose of this research is to implement this mandatory type of sign equipment on the runway in the AGL lab so that it refers to the category 1 and category 2 runway standards. A research method that focuses on the goal of developing a theory in the discipline of airport electrical design. The result of the research is the selection of energy-saving lamp types in flight aids for electrical facilities. The conclusion of the research is the implementation of using a light emitting diode on the Taxyway Guidance Sign refers to the mandatory.